Insights into the interaction between mineral formation and heavy metals immobilization, mediated by Virgibacillus exopolymeric substances - Zulfa Ali Al, Disi (2024)
Heavy metal pollution poses significant risks to both the environment and human health due to their toxicity, long residence times, and their ability to bioaccumulate and bio magnify across the food chain. To address this issue, microbial biomineralization has emerged as a promising approach to the bio-removal of heavy metals through immobilization. This process is facilitated by extracellular polymeric substances (EPS), which also play a crucial role in mediating mineral formation. In this study, the interactions between several selected heavy metals (Cd2+, Cu2+, Ni2+, Zn2+), EPS, and mineral formation were investigated using two mineral-forming Virgibacillus strains isolated from the Qatari sabkhas, which are known to be suitable sites for the formation of biominerals. An additional non-mineral-forming Virgibacillus strain isolated from the Dukhan oil waste dumpsite was also investigated. Cd2+ and Zn2+ were to inhibit mineral formation, likely due to competition with Ca2+ and Mg2+ ions during biomineralization. However, exposure to Ni2+ or Cu2+ resulted in changes in the FTIR spectra of the EPS, suggesting the presence of specific functional group bindings within the EPS matrix. The EPS produced by each strain was also directly associated with their efficiency (%) at removing heavy metals. Notably, the EPS from Virgibacillus halodenitrificans Z4D1, the non-mineral-forming strain, exhibited the highest heavy metal removal efficiency of 31.7 % for Zn2+. These findings reveal that EPS do not only affect the biomineralization process but also that the functional groups in EPS have a direct effect on the immobilization of several heavy metals. Conditions that are not suitable for mineral formation may instead be appropriate for the removal of specific heavy metals.